2017
DOI: 10.1091/mbc.e16-10-0728
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoregulation of Tau modulates inhibition of kinesin-1 motility

Abstract: Regulation of axonal transport includes control of the microtubule-associated protein Tau. Site-specific pseudophosphorylation of Tau modulates its ability to inhibit kinesin-1 motility by both shifting its static–dynamic state binding equilibrium toward the dynamic state and reducing its affinity for microtubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 38 publications
0
101
2
Order By: Relevance
“…Tau is modified by a variety of post‐translational modifications, and over 85 putative phosphorylation sites have been identified . While the function of most of these sites is unknown, phosphorylation of tyrosine 18 weakens tau's affinity to microtubules and in turn the inhibition of kinesin‐1 motility . Thus, multiple layers of regulation allow the cell to tune the local density and dynamics of tau to control trafficking in specific subcellular regions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tau is modified by a variety of post‐translational modifications, and over 85 putative phosphorylation sites have been identified . While the function of most of these sites is unknown, phosphorylation of tyrosine 18 weakens tau's affinity to microtubules and in turn the inhibition of kinesin‐1 motility . Thus, multiple layers of regulation allow the cell to tune the local density and dynamics of tau to control trafficking in specific subcellular regions …”
Section: Discussionmentioning
confidence: 99%
“…The length of the projection domain modulates tau's effect on motor protein motility, with the shortest isoform exhibiting the strongest inhibition . Over 85 putative phosphorylation sites have been identified for tau, and tau phosphorylation modulates the dynamic equilibrium between static and transient binding to the microtubule . Tau phosphorylation is tightly regulated during development and aberrant phosphorylation is linked to disease …”
Section: Introductionmentioning
confidence: 99%
“…Similar to other MAPs reviewed here, it has been demonstrated that tau phosphorylation reduces its affinity for microtubules or its ability to promote microtubule polymerization, resulting in overall microtubule instability (Avila et al, ). Phosphorylation at specific sites, such as Y18, regulates the dynamicity of tau on the microtubule and has significant effects on kinesin‐1 motility (Stern et al, ). Whether neuronal cell death is a consequence of microtubule instability, transport, or tau neurofibrillary tangles is controversial (Dawson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, mitochondrial anterograde transport seems to be more vulnerable in AD . One possible mechanism underlying the more obvious loss of mitochondrial anterograde transport is that tau inhibits kinesin‐1 activity but has little effect on dynein‐based movement . In addition to mitochondrial anterograde motors, mitochondrial anchor protein syntaphilin buds out of axonal mitochondria and is further degraded in AD‐related mutant hAPP Tg neurons, which increases mitochondrial retrograde movements in axons (Figure A,B) .…”
Section: Implications Of Axonal Mitochondrial Transport For Neurologimentioning
confidence: 99%